Quantitative 31P NMR Spectroscopy: Principles, Methodologies, and Applications in Phosphorus-Containing Compound Analysis - Yaqin Liu; Lina Gao; Zeling Yu (Applied Sciences)
Nuclear magnetic resonance (NMR) spectroscopy is gaining prominence as a vital quantitative method for sample analysis, with significant progress being made in the investigation of heteronuclei like phosphorus, a key element in numerous physiological functions. This paper provides a comprehensive review of the principles, methodologies, and applications of quantitative 31P nuclear magnetic resonance (qNMR) spectroscopy. It begins with an introduction to the fundamental principles of NMR spectroscopy, highlighting the specific advantages of qNMR and the unique properties of the 31P nucleus, including its high natural abundance and broad chemical shift range. While 1H qNMR is widely used, signal overlap in complex mixtures can limit its accuracy. Additionally, this work explores diverse applications of 31P qNMR across fields such as food analysis, pharmaceuticals, and biology, emphasizing its contributions to real-time drug quantification, metabolomics, and environmental analysis. A key advantage of 31P NMR is its ability to provide exclusive detection and direct quantification of phosphorus in phosphorus-containing compounds. The internal standard method is favored for its simplicity, as it avoids the need for calibration curves, while the external standard method is better suited for natural products with established reference materials. This review aims to consolidate the applied prospects of 31P qNMR, emphasizing its potential to expand the horizons of quantitative detection technologies and facilitate advancements in future research and practical applications.